Eight New Candidate Multiplanet Systems among TESS Objects of Interest - Mohamed Jassim Munavar Hussain; Michelle Kunimoto (The Astronomical Journal)
We present a search of the TESS Object of Interest (TOI) Catalog for new multiplanet systems. We perform a Box Least Squares search on light curves prepared by the Quick-Look Pipeline to recover known candidates and perform a targeted search for additional candidates in each system. Following vetting and manual inspection, we present eight new planet candidates in multiplanet systems. Highlighted systems include TOI-2037 and TOI-6543, each displaying a nearness to a 2:1 orbital resonance. Four candidates in the TOI-5624 system, including our candidate TIC 53498154.02, have gained TOI status. If confirmed, the TOI-5624 system becomes the 29th known five-planet system. Our identification of candidate TIC 302305400.02 in the TOI-5487 system presents an interesting case study for the formation of hot Jupiter systems, potentially marking the first known system harboring a close-in giant outer companion to an existing hot Jupiter.